COMMISSIVE SPEECH ACTS FOUND IN "ONWARD" MOVIE BY DAN SCANLON - Desica, Desica; Ambalegin, Ambalegin (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2021)
This research aimed to find out the types of commissive acts found in the movie entitled Onward as the data source. The utterances uttered by the characters in the movie were taken as the data of the research and classified them by using the theory of commissive acts proposed by Searle. This research is a descriptive qualitative research, as to describe the data in words and sentences. To collect the data, researchers conducted observational method and non-participatory technique. The researchers used the method of pragmatic identity to analyse the data and pragmatic competence – in equalizing technique to equalized the data based on the theory used. The research result showed that there were 17 utterances of commissive acts found in Onward movie. They were 2 data of promising, 4 data of threatening, 2 data of accepting, 6 data of refusing, and 2 data of offering. The act of refusal was the frequently used type of commissive acts since the character had the habit of not wanting to bother other people.